Habitus and Cultural Capital of Muslim Women: Empowerment of Women in Nasyiatul ‘Aisiyah Gamping, Yogyakarta - Siti Nur Amanah; Adib Khairil Musthafa (An-Nida')
This article discusses the Muslim women's empowerment movement carried out by Nasyiatul ‘Aisyiyah Gamping, Yogyakarta, within the landscape of gender justice, addressing issues surrounding women such as female religious scholars, women's participation in public spaces, and the cultural roles of women in society. The capital and habituation of Muslim women in this article are positioned as both theoretical and practical implications of the women's empowerment movement. This study employs a qualitative research approach with a case study focus on the women's organization Nasyiatul ‘Aisyiyah Gamping, Yogyakarta. The findings reveal that the cultural capital and habituation of women are implemented by Nasyiatul ‘Aisyiyah Gamping through empowerment movements in three dimensions: structural, cultural, and individual knowledge bases. In the structural dimension, women's participation is reflected in their active involvement in the organization's activities. In the cultural dimension, it is evident in women's participation in religious activities within the Gamping community. At the individual level, it is demonstrated through Muslim women's access to knowledge on issues related to gender justice. Although the women's empowerment movement may appear to be part of a broader social transformation movement, significant challenges persist. The challenges in this empowerment movement and the efforts to establish the habituation of Muslim women remain a long-term endeavor for Nasyiatul Aisyiyah. These challenges include both structural and cultural dimensions. The deeply rooted patriarchal epistemology among some members of the organization and the broader Gamping community further illustrates the complexities of achieving gender justice, even at the local level.